Comparing the Effectiveness of CBT and Acceptance and Commitment Therapy on the Temptation of Patients Undergoing Addiction Treatment in Khorramshahr - Heibeh Ziaee; Emad Yosefi; Leila khajehpoor (Iranian Evolutionary Educational Psychology Journal)
Objective: The objective of the current investigation was to conduct a comparative analysis of the efficacy of cognitive behavioral therapy and acceptance and commitment-based therapy in managing the impulses experienced by individuals receiving treatment for addiction in Khorramshahr. Methods: This study utilized a quasi-experimental approach employing a pre-test and post-test design with a control group. The study cohort for this investigation was comprised of 45 individuals undergoing drug cessation, who were chosen randomly from the pool of drug-dependent individuals seeking assistance at addiction treatment facilities in Khorramshahr. Subsequently, they were randomly allocated into three cohorts of 15 individuals each, with one group serving as the control (15 individuals) and two others receiving either acceptance and commitment therapy or cognitive-behavioral therapy. Data gathering was executed through the utilization of a questionnaire designed to assess drug use temptations post-treatment, as outlined by Federdi et al. (2008). Results: The outcomes of the study demonstrated the effectiveness of CBT and ACT in diminishing the temptations experienced by individuals undergoing addiction treatment in Khorramshahr. Furthermore, the findings indicated no significant difference between ACT and CBT in reducing temptations among individuals undergoing addiction treatment in Khorramshahr. Conclusions: In conclusion, it is recommended that both interventions be implemented to mitigate the temptations experienced by individuals undergoing addiction treatment.